Gold Nanorods Targeted to Delta Opioid Receptor: Plasmon-Resonant Contrast and Photothermal Agents - Kvar C. Black; Nathaniel D. Kirkpatrick; Timothy S. Troutman; Liping Xu; Josef Vagner; Robert J. Gillies; Jennifer K. Barton; Urs Utzinger; Marek Romanowski (Molecular Imaging)
Molecularly targeted gold nanorods were investigated for applications in both diagnostic imaging and disease treatment with cellular resolution. The nanorods were tested in two genetically engineered cell lines derived from the human colon carcinoma HCT-116, a model for studying ligand-receptor interactions. One of these lines was modified to express delta opioid receptor (δOR) and green fluorescent protein, whereas the other was receptor free and expressed a red fluorescent protein, to serve as the control. Deltorphin, a high-affinity ligand for δOR, was stably attached to the gold nanorods through a thiol-terminated linker. In a mixed population of cells, we demonstrated selective imaging and destruction of receptor-expressing cells while sparing those cells that did not express the receptor. The molecularly targeted nanorods can be used as an in vitro ligand-binding and cytotoxic treatment assay platform and could potentially be applied in vivo for diagnostic and therapeutic purposes with endoscopic technology.